Mogut li aerobnye uprazhneniya umerennoi intensivnosti vyzyvat' polozhitel'nye izmeneniya v faktorakh svertyvaniya i fibrinoliza? - Mavrovuniotis, F. H.; Argiriadou, E. A.; Sofiadis, N. T.; Kougioumtzidis, C. P. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The authors of this paper studied the effect of submaximal aerobic exercise on coagulation and fibrinolysis factors, and expecially on thrombin - àntithrombin (TAT) and plasmin - antiplasmin (PAP). 35 males, who participated in the research, divided in two groups, athletes and inactive persons. Blood had been drawn before and immediately after exercise. The results showed favourable changes on TAT and PAP and similar response for the groups.